The effect of a backrest and seatpan inclination on sitting discomfort and trunk muscle activation in subjects with extension-related low back pain - Curran, M.; Dankaerts, W.; O'Sullivan, Peter; O'Sullivan, L.; O'Sullivan, Keiran (Taylor & Francis Ltd., 2014)
Few studies have demonstrated that seating modifications reduce low back pain (LBP). One recent study found that a forward-inclined seatpan reduced low back discomfort (LBD), however this was only examined in people with flexion-related LBP. No study has yet investigated its effectiveness among people with extension-related LBP. This crossover study examined 12 subjects with extension-related LBP. Sitting discomfort and surface electromyography of three trunk muscles were recorded during a 10-minute typing task while sitting with two different seatpan inclinations, both with and without a backrest. LBD (p < 0.001) and overall body discomfort (OBD) ( p = 0.016) were significantly greater on the forward-inclined seatpan. The backrest did not alter trunk muscle activation or sitting discomfort. The results demonstrate that in a specific subgroup of people with extension-related LBP, increasing forward seatpan inclination significantly increased LBD and OBD. Future research should consider matching ergonomics prescriptions according to the individual presentation of people with LBP. Practitioner Summary: Sitting on a forward-inclined seatpan resulted in greater low back discomfort and overall body discomfort than sitting on a flat seatpan during a typing task among people with extension-related low back pain (LBP). Future research should examine matching ergonomics prescriptions to the individual presentation of people with LBP.